2014
DOI: 10.1039/c3nr04835g
|View full text |Cite
|
Sign up to set email alerts
|

Protein-directed synthesis of pH-responsive red fluorescent copper nanoclusters and their applications in cellular imaging and catalysis

Abstract: The development of functional copper nanoclusters (Cu NCs) is becoming increasingly widespread in consumer technologies due to their applications in cellular imaging and catalysis. Herein, we report a simple protein-directed synthesis of stable, water-soluble and fluorescent Cu NCs, using BSA as the stabilising agent. Meanwhile, in this study, hydrazine hydrate (N₂H₄·2H₂O) was used as the reducing agent. N₂H₄·2H₂O was a mild reducing agent suggesting that all processes could be operated at room temperature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
181
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 47 publications
4
181
0
Order By: Relevance
“…3). BSA-capping fluorescent metal NCs displayed good dispersion and high stability in aqueous phase [26,27]. Especially, BSA has a much-stronger affinity toward metal ions, including Pb 2+ , which is important for practical applications in ion detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). BSA-capping fluorescent metal NCs displayed good dispersion and high stability in aqueous phase [26,27]. Especially, BSA has a much-stronger affinity toward metal ions, including Pb 2+ , which is important for practical applications in ion detection.…”
Section: Resultsmentioning
confidence: 99%
“…As-prepared Ag/Au alloy NCs were protected by bovine serum albumin (BSA) which could work as an important scaffold to prevent NCs from growing large NPs [25]. More importantly, NCs stabilized by BSA exhibited good dispersion and high stability in aqueous solution [26,27]. These advantages illustrated that the resultant alloy NCs were promising fluorescent probes for detection of heavy-metal ions.…”
Section: Introductionmentioning
confidence: 93%
“…Until now, extensive studies have concentrated on the synthesis of luminescent and water-soluble metal nanoclusters using various types of templates or stabilizing agents such as peptides , proteins (Wang et al, 2014a), DNA (Copp et al, 2014), polymers (Shang and Dong, 2008), dendrimers (Tanaka et al, 2011) and thiols (Wu et al, 2009). Experimentally, largely excessive templates were required to stabilize nanoclusters or reduce metal salts to form template-protected metal clusters.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics partly originate from their large specific surface area, which is due to their small sizes [9][10][11][12][13][14][15]. Through stabilization of protective agents, it has been shown that the stability and fundamental properties of noble metal NPs can be significantly enhanced [16,17].…”
Section: Introductionmentioning
confidence: 99%